Emotional practices: how masking negative emotions impacts the post-acquisition integration process - Vuori, Natalia; Vuori, Timo O.; Huy, Quy N. (Strategic Management Journal, 2018)
[Research summary: We conducted a real-time field study of a post-acquisition integration process. We identified two practices that contributed to integration failure. First, the practice of masking negative emotions caused members of both firms to perceive that the partner firm's members were satisfied with the integration process, even though they were not. These false perceptions of satisfaction resulted in minimal corrective actions, the escalation of the situation, and ultimately, integration failure. Second, efficiency-driven communication practices used in interfirm communication exacerbated the effect of masking negative emotions on false perceptions of satisfaction by shielding both firms' members from the other firm's members' spontaneous emotional reactions. Our research invites scholars to consider more deeply the emotional consequences of various common organizational practices. Managerial summary: Do you disagree with your employee, manager, or business partner? Does this disagreement make you annoyed or even angry? Yet, you decide to mask your negative emotions and discuss the disagreement with a neutral or happy face. Wrong. We find that masking negative emotions in the work environment can prevent corrective actions, escalate disagreement, and make people to develop long-lasting negative sentiments toward the counterpart that ultimately result in dysfunctional behaviors. Our findings further reveal that commonly used organizational practices such as communicating via email may contribute to the deliberate masking of negative emotions. We suggest that managers should carefully review if and how their organization's practices prevent or enable people to share their emotions authentically to ensure timely corrective actions and proactive development of business operations.]